2019
DOI: 10.3390/app9245495
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Effect of Vortex Generator Spacing on Boundary Layer Flow Separation Control

Abstract: During the operation of wind turbines, flow separation appears at the blade roots, which reduces the aerodynamic efficiency of the wind turbine. In order to effectively apply vortex generators (VGs) to blade flow control, the effect of the VG spacing (λ) on flow control is studied via numerical calculations and wind tunnel experiments. First, the large eddy simulation (LES) method was used to calculate the flow separation in the boundary layer of a flat plate under an adverse pressure gradient. The large-scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Firstly, the clean airfoil curve shows its maximum peak before arriving to 12.45 • of AoA. However, when the DU97W300 has a VG on its suction side, the C L curve remains growing, as it is the principal effect of a VG implementation [28,29]. On the other hand, if the optimum GF length is applied for each AoA, higher C L values are reached for angles close to 0 • .…”
Section: Discussionmentioning
confidence: 98%
“…Firstly, the clean airfoil curve shows its maximum peak before arriving to 12.45 • of AoA. However, when the DU97W300 has a VG on its suction side, the C L curve remains growing, as it is the principal effect of a VG implementation [28,29]. On the other hand, if the optimum GF length is applied for each AoA, higher C L values are reached for angles close to 0 • .…”
Section: Discussionmentioning
confidence: 98%
“…The distance between the VG pairs (λ) and the angle of attack (α) of the VG were specified as 6 • and 11 • for efficiency. The recommended λ/h investigated through a flat-plane CFD analysis study is 5 [32]. The VGs are installed on the suction surface and at the root of the blade to enhance the aerodynamic performance.…”
Section: Methodsmentioning
confidence: 99%
“…There is also a third case when it is attached to the edge of the vehicle, these are known as flaps (see Figure 4c). The offset between two delta shaped winglets was examined in the work by Li et al [80]. They concluded that the maximum drag reduction was achieved at 5 offset distance/VG height ratio.…”
Section: Topology Modificationmentioning
confidence: 99%